Levodopa treatment in Parkinson’s disease: earlier or later? - Paoletti, Federico Paolini; Tambasco, Nicola; Parnetti, Lucilla (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
More than 50 years after its introduction, levodopa is still considered the mainstay of treatment of Parkinson’s disease (PD) and remains the gold standard against which new therapies must be measured (1). As the most effective drug for PD, a single oral dose of levodopa is able to ameliorate dramatically motor signs providing benefits on deftness, gait and speech for a limited period of time known as on time (2). However, when levodopa should be started is still a matter of debate.